The Relationship between Inflation, Exchange Rate, and Currency Substitution: Evidence from Panel Vector Error Correction Model Approach - Srithilat, Khaysy; Sun, Gang; Chanthanivong, Thongphet; Thavisay, Maketta (International Journal of Economics and Financial Issues, 2018)
This study investigates the relationship between inflation, real exchange rate, and currency substitution in Southeast Asian economies based on the panel Vector Error Correction Model. Regarding the panel unit root testing result indicates that variables are stationary in the first difference which appropriate to be utilized of panel VECM technique. The empirical results suggest that there exists panel cointegration and long-run relationship between inflation, real exchange rate and currency substitution. Moreover, the evidence from both Fully Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square DOLS also confirmed the existence of long-run association between variables. Increasing of inflation rate and devaluation of domestic currency positively effect on currency substitution in the long-run. Furthermore, the result of short-run causal relationship based on panel Granger causality reveals the bidirectional relationship between inflation and currency substitution and unidirectional relationship between exchange rate and currency substitution in Southeast Asia. Keywords: currency substitution, inflation rate, exchange rate, monetary policy, panel VECM JEL Classifications: E31, E52, F31